2019
DOI: 10.1016/j.ijbiomac.2018.11.265
|View full text |Cite
|
Sign up to set email alerts
|

MFG-E8 induced differences in proteomic profiles in mouse C2C12 cells and its effect on PI3K/Akt and ERK signal pathways

Abstract: Milk fat globule-EGF factor 8 (MFG-E8) is one of the major proteins in milk fat globule membrane. In this study, mouse-derived C2C12 myoblast cells were served as an experimentally tractable model system for investigating the molecular basis of skeletal muscle cell specification and development. To examine the biochemical adaptations associated with myocytes formation comprehensively, a liquid chromatography coupled with tandem mass spectrometry label-free semi-quantitative approach was used to analyse the myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…The MFG-E8 was extracted using an electric cream separator, and separated according to cellulose DEAE-52 ion exchange chromatography method. Our previous work has demonstrated that MFG-E8 can promote cell proliferation and differentiation via the PI3K/Akt and ERK signal pathway in the in vitro C2C12 cells (Li et al 2019). In this study, we focused on the in vivo rat experiment to investigate the effect of MFG-E8 on age-related sarcopenia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MFG-E8 was extracted using an electric cream separator, and separated according to cellulose DEAE-52 ion exchange chromatography method. Our previous work has demonstrated that MFG-E8 can promote cell proliferation and differentiation via the PI3K/Akt and ERK signal pathway in the in vitro C2C12 cells (Li et al 2019). In this study, we focused on the in vivo rat experiment to investigate the effect of MFG-E8 on age-related sarcopenia.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated in vitro C2C12 cells that MFG-E8 could promote cell proliferation and differentiation (He et al 2017;Li et al 2017). Based on the results of cell differential proteomics, we clarified that MFG-E8 promoting cell proliferation is related to 60S ribosomal protein L29, Hsp 40, integrin α-V, serine/threonine protein phosphatase 2A and insulin degrading enzyme expression, mediating PI3K, MAPK, AMPK and Oxidative phosphorylation signaling pathways cascade, and PI3K plays a major role (Li et al 2019). In vitro experiment preliminarily demonstrated the possible benefits of MFG-E8 on sarcopenia (Li et al 2018).…”
mentioning
confidence: 79%
“…Milk fat globule-EGF factor 8 MFG membrane proteins, predominantly MFG epidermal growth factor 8 (MFG-E8, also known as lactadherin), stimulates cell proliferation through the PI3K/AKT/mTORC1 signaling pathway [324][325][326][327] . Increased levels of MFG-E8 found in tissue and plasma exosomes from PCa patients have been compared with controls [327,328] .…”
Section: Palmitic Acidmentioning
confidence: 99%
“…Recent evidence indicates that protein palmitoylation is potentially involved in palmitate-induced mTORC1 activation, whereas 2-bromopalmitate, a protein palmitoylation inhibitor, ameliorated palmitate-triggered mTORC1 activation [110]. Furthermore, MFG membrane proteins, predominantly MFG-E8, promote cell proliferation through the PI3K/AKT/mTORC1 signaling pathway [111,112].…”
Section: Milk Lipidsmentioning
confidence: 99%